Leaf litter breakdown rates and associated fauna of native and exotic trees used in neotropical riparia reforestation (2014)
ABSTRACT A signature of globalization is the prevalence of exotic trees along reforested urban and rural riparian zones in the Neotropics, but little is known about the instream processing of its leaf litter. In this study, leaf litter breakdown rates were measured during 35 days using mesh bags within a reference headwater stream for seven exotic and three native tree species commonly used in urban and rural reforestation. Artocarpus altilis, Schefflera actinophylla and Terminalia catappa scored the highest mass loss rates ( and gt;85 %; mean life: t50 85 %; vida media: t50